Donation After the Circulatory Determination of Death: Some Responses to Recent Criticisms. Issue 2 (13th March 2018) - McGee, Andrew; Gardiner, Dale
Abstract: This article defends the criterion of permanence as a valid criterion for declaring death against some well-known recent objections. We argue that it is reasonable to adopt the criterion of permanence for declaring death, given how difficult it is to know when the point of irreversibility is actually reached. We claim that this point applies in all contexts, including the donation after circulatory determination of death context. We also examine some of the potentially unpalatable ramifications, for current death declaration practices, of adopting the irreversibility criterion.